Variation of lung fissure completeness and sex-based differences in lung anatomy using cadaveric lungs - Nicholas R. Stange; Shivika Ahuja; Daniel T. Daly; Yun Tan (Translational Research in Anatomy)
The gross anatomy of human lungs is relatively consistent; however, previous studies have noted variations in the degree of fissure completeness as well as sex-based differences in lung size and shape. In this study, 90 cadaveric lungs obtained through the Gift Body Program of Saint Louis University School of Medicine were used to describe the linear dimensions and fissure completeness of fixed cadaveric lungs, provide a detailed and reproducible method of measuring dimensions of lungs, and describe sex-related differences in lung dimensions. This study adds to the existing body of knowledge of lung anatomy from studies conducted via CT imaging, thoracic dimension analysis, pulmonary function testing, and other cadaveric studies. For dimensional analysis and fissure completeness, the right horizontal fissure exhibited the most variations in the fissures of the lung. For sex-based differences, female left lungs had a similar height, a narrower base, and a more oblique angle when compared to male lungs. No significant differences in oblique angle, horizontal angle or width to height ratios were observed. This is the first cadaveric study to demonstrate sex-based differences in human lungs and supports the reliability of using cadaveric specimens to study the clinical implications of anatomical variations.